2015
DOI: 10.1111/jce.12821
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Atrial Electromechanical Delay in Predicting Atrial Fibrillation in Myotonic Dystrophy Type 1 Patients

Abstract: Our results showed that the echocardiographic atrial electromechanical delay indices (intraleft and inter-AEMD) were significantly increased in DM1 subjects with normal cardiac function. Intraleft and inter-AEMD represent noninvasive, inexpensive, useful and simple parameters to assess the AF risk in DM1 patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
14
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 45 publications
(72 reference statements)
4
14
1
Order By: Relevance
“…3 We recently observed an atrial fibrillation (AF) prevalence of 30% in the DM1 population who underwent long-period (30 days) external loop recorder (ELR) monitoring performed every 6 months during a 4-year followup. 4 These data confirmed the high prevalence of atrial high-rate episodes detected by pacemaker (PM) diagnostics in DM1 patients who underwent device implantation and considered a surrogate of atrial fibrillation. 5 doi: 10.1111/pace.12970…”
Section: Which Is the True Epidemiology Of Atrial Fibrillation In Myosupporting
confidence: 67%
See 3 more Smart Citations
“…3 We recently observed an atrial fibrillation (AF) prevalence of 30% in the DM1 population who underwent long-period (30 days) external loop recorder (ELR) monitoring performed every 6 months during a 4-year followup. 4 These data confirmed the high prevalence of atrial high-rate episodes detected by pacemaker (PM) diagnostics in DM1 patients who underwent device implantation and considered a surrogate of atrial fibrillation. 5 doi: 10.1111/pace.12970…”
Section: Which Is the True Epidemiology Of Atrial Fibrillation In Myosupporting
confidence: 67%
“…Atrial fibrillation is a common finding on 12‐lead ECG or 24‐hour Holter monitoring, often asymptomatic, with a prevalence up to 17% in DM1 population and it is associated with a significant risk of death in association with the DM1 patients’ age . We recently observed an atrial fibrillation (AF) prevalence of 30% in the DM1 population who underwent long‐period (30 days) external loop recorder (ELR) monitoring performed every 6 months during a 4‐year follow‐up . These data confirmed the high prevalence of atrial high‐rate episodes detected by pacemaker (PM) diagnostics in DM1 patients who underwent device implantation and considered a surrogate of atrial fibrillation…”
supporting
confidence: 60%
See 2 more Smart Citations
“…27 It has been studied in some clinical conditions, [28][29][30][31] and it was found that AEMD is significantly correlated with the prolonged maximum P-wave duration, P-wave dispersion, and degree of histopathological changes. [32][33][34] Previous studies evaluated the predictive role of intra-left atrial electromechanical delay for paroxysmal atrial fibrillation recurrence after cardioversion, [35][36][37] lone atrial fibrillation attack, 38 new-onset AF after acute myocardial infarction, 39 occurrence of atrial arrhythmias in adult patients with congenital heart diseases, 40 myotonic dystrophy type 1, 41 and atrial septal aneurysm. 42…”
Section: Discussionmentioning
confidence: 99%